Introduction to small molecule drug discovery and preclinical development - Southey, Michelle W. Y.; Brunavs, Michael (Frontiers in Drug Discovery, 2023)
Over 90% of marketed drugs (Makurvet 2021) are small molecules, low molecular weight organic compounds that have been discovered, designed, and developed to prompt a specific biological process in the body. Examples include antibiotics (penicillin), analgesics (paracetamol) and synthetic hormones (corticosteroids). On average, it takes 10-15 years to develop a new medicine from initial discovery through to regulatory approval and the total cost is often in the billions (DiMasi, Hansen and Grabowski 2003). For every drug that makes it to the market, there are many more that do not, and it is the outlay associated with abortive efforts that accounts for most of this expense. The discovery of new drugs remains a significant challenge, involving teams of researchers from chemistry, biology, drug development, computer science and informatics. In this article we will discuss the key concepts and issues encountered in small molecule preclinical drug discovery and introduce some of the emerging technologies being developed to overcome current obstacles.